Bimbingan Islam Dengan Metode Dzikir Pada Narapidana Wanita Kasus Kekerasan Pada Anak Di Lapas Banyuwangi - Khairiyah, Royatul; Yohandi; Sulaiman, A. Husam (CV. SINAR HOWUHOWU, 2025)
This study aims to understand the effectiveness of Islamic guidance through the dhikr method in the spiritual and psychological rehabilitation of female inmates convicted of child abuse in Banyuwangi Prison, focusing on the individual case of Mrs. R. The study used a qualitative case study approach, using data collection techniques such as in-depth interviews, participatory observation, and documentation. The results showed that prior to the guidance, Mrs. R experienced severe emotional stress due to a stressful life history, family conflict, and physical and psychological exhaustion from dealing with her child’s behavior. The implementation of dhikr, which included congregational prayer, night prayer, wirid (recitation of prayer), istighfar (repentance), and Quranic recitation, significantly impacted her inner peace, improved emotional control, the emergence of an attitude of sincerity (Ikhlas), decreased excessive guilt, and increased motivation to improve her relationships with her children. The prison environment, which supports religious activities, also accelerated the mental recovery process. This study concluded that Islamic guidance through the dhikr method is effective as a means of spiritual rehabilitation for female inmates, as it stabilizes emotional states, increases self-awareness, and helps develop a more positive personality for life after release.